Comment rester vigilant face à l’oubli ? Le musée de la fonderie à Rosières - Guillaume Etienne (Conserveries Mémorielles)
More and more museums are dedicated to local histories of work and labour, displaying industrial artefacts and objects directly taken from the work place. In such museums, the visitors do not only get a chance to discover specific techniques and savoir-faire. The purpose is also to expose them to a much encompassing cultural experience. In the local museum of Rosières, a small industrial town located in the centre of France, the visitors are offered much more than the possibility to get a grasp of the smelting work itself, which we demonstrate through an analysis of the history of this museum, of the content of its permanent exhibition, and of a network of individuals who try to keep the industrial memory of this area alive. This museum indeed appears to function as a microcosm of a social life that no longer exists, and that was strongly connected to the factory life and the industrial plant as well as industrial paternalism that ruled the workers’ lives during almost one and a half century.